Desenvolvimento de classes de teste para a camada de persistência do framework de preço de venda (FrameMK) usando JUnit - Ribas, Jonathan Heverson (2014)
The unit test allows evaluating the smallest system unit, which is the class within object orientation. Its objective is allowing the error identification in the business logic inside this unity. This paper performed unit tests in a Framework of sell price formation (FrameMK) which is developed by the Research Group in Information Systems. The test creation is made by an adaptation of one methodology intended to test application, which provided the creation of test cases. From this test cases, was been created the test classes in the JUnit tool, to the framework persistence layer. Finally, with the test classes was possible to evaluate the method scenarios, which help to increase the system confiability and the possible functionality insertions.